Electrochemical, photocatalytic and sensor studies of clay/MgO nanoparticles - M. Mylarappa; N. Raghavendra; B.S. Surendra; K.N. Shravana Kumar; S. Kantharjau (Applied Surface Science Advances, 2022)
We propose a method for producing cost-effective Clay-metal oxide (Clay/MgO nanocomposite) by chemical solution combustion process using urea as a fuel. X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM) were used to explore the structural characteristics of Clay/MgO nanocomposite. The spinel/cubic structure of the synthesized Clay/MgO nanocomposite was confirmed by XRD patterns. When the Clay was modified with MgO, FE-SEM micrographs revealed homogeneous sphere-shaped MgO. Clay/MgO nanocomposite photocatalytic performance was investigated for its possible role in the photo degradation of Rhodamine-B (Rh-B) dye under UV light. The result indicates that the composite is suited for good photocatalytic degradation performance, with a 90% degradation rate. The produced compound was subjected to electrochemical examination using a constructed electrode in 0.1 M KOH electrolyte. It worked well in redox potential measurements using cyclic voltammetry and they expanded their sensor operations, which included chemical and biomolecule sensors (Stannous Chloride Sensor, biomolecules (Dextrose), and eye drop chemicals). These studies revealed a novel platform for synthesizing Clay/MgO nanocomposite using a simple chemical process for various applications such as heavy metal detection, wastewater treatment, and electrochemical experiments.